2-chains and square roots of Thompson's group F. (September 2020) - KOBERDA, THOMAS; LODHA, YASH
Abstract : We study 2-generated subgroups f, g<Homeo^+(I) such that f^2, g^2 is isomorphic to Thompson's group F, and such that the supports of f and g form a chain of two intervals. We show that this class contains uncountably many isomorphism types. These include examples with non-abelian free subgroups, examples which do not admit faithful actions by C^2 diffeomorphisms on 1-manifolds, examples which do not admit faithful actions by PL homeomorphisms on an interval, and examples which are not finitely presented. We thus answer questions due to Brin. We also show that many relatively uncomplicated groups of homeomorphisms can have very complicated square roots, thus establishing the behavior of square roots of F as part of a general phenomenon among subgroups of Homeo^+(I) .